Application Of Underwater Lamp For Bagan Tancap At Lekok - Sukandar Sukandar (Journal of Innovation and Applied Technology, 2015)
ABSTRACTBaganis one type of fishing gear that uses light to collect fish. The lights are expected to stimulate the fish to come and stay around the light and than arrested with net. The use of light for fishing is growing rapidly, almost all fishing gear use light as a tool for collecting fish. Application of this technology aims to increase fish catch fishermen in District Lekok through the application of technology underwater lamp with LED. Underwater lamp applied to the bagantancapwith a certain intensity and color to find the intensity of light and color that give the best catches.Best catches in the light of 450 lux is capable of delivering the highest total catch of 254 kg, it is supported by the values of illumination of 1.5 lux at a distance of 5 m. Types of fish that were caught on as much as 23 step chart types where the type of Stolephorus spp, Selaroides spp, Leiognathus spp, Loligo sp, Rastrelliger spp is a type of fish that always caught each fishing operationKeywords: lamp, bottom, tools, bagan, Lekok